2020
DOI: 10.3390/educsci10120366
|View full text |Cite
|
Sign up to set email alerts
|

How Can Flipped Classroom Approach Support the Development of University Students’ Working Life Skills?—University Teachers’ Viewpoint

Abstract: Higher education students need both generic skills and field-specific knowledge in order to cope with the diverse demands of working life. The aim of this study was to gain a better understanding of the development of university students’ working life skills and of how these skills can be developed in learning environments utilizing the flipped classroom approach. The focus was on the experiences and thoughts of higher education teachers concerning which learning environment features support the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
10
0
4
Order By: Relevance
“…In other words, using FL without the necessary learning skills or experiences of online teaching and technology may be challenging for students. Thus, it is suggested that starting from the more teacherdirected flipped classroom may be more effective than directly using FL (Väisänen & Hirsto, 2020). Both negative and positive results have been identified in previous studies (e.g., Akçayır & Akçayır, 2018;O'Flaherty et al, 2015).…”
Section: Online Teaching Flipped Learning and Learning Analyticsmentioning
confidence: 78%
“…In other words, using FL without the necessary learning skills or experiences of online teaching and technology may be challenging for students. Thus, it is suggested that starting from the more teacherdirected flipped classroom may be more effective than directly using FL (Väisänen & Hirsto, 2020). Both negative and positive results have been identified in previous studies (e.g., Akçayır & Akçayır, 2018;O'Flaherty et al, 2015).…”
Section: Online Teaching Flipped Learning and Learning Analyticsmentioning
confidence: 78%
“…The research experience indicated that incorporating project-based practical activities has a positive impact on student learning, motivation, and performance both in the short and long term [52]. In addition, incorporating a research project expands students' knowledge and boosts their real-life skills, which encourages the formation and development of real-life competencies.…”
Section: Discussionmentioning
confidence: 99%
“…From its inception, the Flipped Classroom method has been based on taking theory teaching out of the classroom and allowing students to obtain theoretical concepts before entering the classroom [31,32]. As a result, during class, students engage in active and cooperative learning based on their prior experience [33,34].…”
Section: Layer 1-learning Methodologymentioning
confidence: 99%